Continuity of Industrial Landscape: From Sümerbank Kayseri Textile Factory to AGU Sumer Campus - Kevseroğlu, Özlem; Kıdık, Ayşegül; Asiliskender, Burak (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2020)
Cultural landscapes explain the evolution of human society and settlement under the influence of the physical constraints and or opportunities offered by the natural environment. It is possible to understand this evolution of industrial landscape by exposing the public memory of its time. Industrial and cultural landscape gives information about the production technology of it’ period and also clue about the settlement areas where the labor force that provides the production in the industrial landscape realizes the housing and socio-cultural activities. In this study Kayseri Sümerbank Textile Factory was selected as a case study, which had continued its function as a factory until 1999, then came to life as a university in 2014. In this study; cultural mapping that will reflect the daily life activities to be created after the in-depth interviews and participatory drawing techniques with the user group who have experienced the factory life in the past and experiencing the university campus life nowadays, then these data will be overlapped and visualized in a digital interface. The result of the study could show us to the continuity of the settlement between the past and present, changing daily life patterns depending on the changing function.